1999
DOI: 10.1002/(sici)1097-0134(19990215)34:3<341::aid-prot7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Finding local structural similarities among families of unrelated protein structures: A generic non-linear alignment algorithm

Abstract: We have developed a generic tool for the automatic identification of regions of local structural similarity in unrelated proteins having different folds, as well as for defining more global similarities that result from homologous protein structures. The computer program GENFIT has evolved from the genetic algorithm-based three-dimensional protein structure comparison program GA_FIT. GENFIT, however, can locate and superimpose regions of local structural homology regardless of their position in a pair of struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Second priority 1 : RMSD • S2 Alignment size and RMSD based score 2 : 3 100 N − RMSD • S3 Structal (Subbiah et al, 1993) score function: (Lethonen et al, 1999) (Lu, 2000) score function no. 1:…”
Section: Scoring Of Similaritymentioning
confidence: 99%
“…Second priority 1 : RMSD • S2 Alignment size and RMSD based score 2 : 3 100 N − RMSD • S3 Structal (Subbiah et al, 1993) score function: (Lethonen et al, 1999) (Lu, 2000) score function no. 1:…”
Section: Scoring Of Similaritymentioning
confidence: 99%
“…Other methods, such as GENE FIT of Lehtonen et al 4 and the approach of Poirrette et al 5 use genetic algorithms to optimally superimpose proteins in identified substructure ranges. All these approaches only use descriptors for the shape of the protein.…”
Section: Introductionmentioning
confidence: 75%
“…Thus, during the recent decade, many heuristic methods have been proposed using various techniques: Monte Carlo optimization [DALI 5., 10.], Dynamic programming [STRUCTAL ( 11 ), LOCK ( 12 )], Graph theory [VAST 13., 14., SARF2 ( 15 )], Combinatorial extension of alignment path [CE ( 16 )], Geometric hashing [MASS ( 17 )], Hidden Markov models [SCALI ( 6 )], Genetic algorithm [Ref. 18., 19.; K2 ( 7 )], Clustering-based method [FAST ( 20 )], and so on. The review can be found in the work by Signh and Brutalg (http://cmgm.stanford.edu/~brutlag/Papers/singh00.pdf).…”
Section: Introductionmentioning
confidence: 99%